Optimalisasi Madrasah Digital melalui Implementasi Transformasi Digital di MTs Negeri 5 Sleman - Busyroni Majid (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
The goal that will be achieved in this study is to find out the optimization of madrasah digitalization learning carried out by teachers, students, and parents using the MS Office 365 A1 series platform. This research uses survey-based action research methods. The achievements obtained in optimizing digital madrasahs in semesters 1 and 2 of the 2021/2022 academic year at MTs Negeri 5 Sleman using Office 365 are as follows; 1) the quantity of Office 365 usage has not changed; 2) Teams Meeting usage increased by 10.60%; 3) student participation rate increased by 17.25%; 4) the use of Office 365-provided applications increased by 79.29%; and 5) the comfort level of using Office 365 increased by 10.33%. From the results obtained, it shows that Office 365 is one of the madrasah digitization applications that suits the needs of madrasahs.